Zending and Culture of Tolaki Tribe in Southeast Sulawesi, 1916-1942 - Basrin Melamba; Nina Herlina; Widyo Nugrahanto; Aswati Mukadas (Jurnal Sejarah Citra Lekha, 2019)
This study analyses the cultural problems as the entity of Tolaki Tribe about Christianity in Southeast Sulawesi in the period 1916-1942. The historical method is used to find and identify the cultural problems that detained the Christianity process by occupying the four stages begins with heuristic, critic, interpretation, until historiography. During the period also, found a pattern of negotiations between traditions or customs and the teachings of Christianity that were played by the evangelists. So, there was a harmonious dialogue between Christians and the indigenous people. In this case, the agent or pastor succeeded in carrying out interactions and playing on the strategies and rules of religion with the provisions of the indigenous people. It was concluded that culture became an obstacle and challenge in the process of Christianity. However, at the same time, it became an opportunity used by the evangelists in the process of spreading religion among the Tolaki society. The culture and religion of Protestant Christian are always united and together in the reality of the living in indigenous people.